Evaluation of the Lower Punctum Parameters and Morphology Using Spectral Domain Anterior Segment Optical Coherence Tomography - Riham S. H. M. Allam; Rania A. Ahmed (Journal of Ophthalmology)
Purpose. To study features of the lower punctum in normal subjects using spectral domain anterior segment optical coherence tomography (SD AS-OCT). Methods. Observational cross-sectional study that included 147 punctae (76 subjects). Punctae were evaluated clinically for appearance, position, and size. AS-OCT was used to evaluate the punctal shape, contents, and junction with the vertical canaliculus. Inner and outer diameters as well as depth were measured. Results. 24 males and 52 females (mean age 44±14.35 y) were included. Lower punctum was perceived by OCT to be an area with an outer diameter (mean 412.16±163 μm), inner diameter (mean 233.67±138.73 μm), and depth (mean 251.7±126.58 μm). The OCT measured outer punctum diameter was significantly less than that measured clinically (P: 0.000). Seven major shapes were identified. The junction with the vertical canaliculus was detectable in 44%. Fluid was detected in 34%, one of which had an air bubble; however, 63% of punctae showed no contents and 4% had debris. Conclusions. AS-OCT can be a useful tool in understanding the anatomy of the punctum and distal lacrimal system as well as tear drainage physiology. Measuring the punctum size may play a role in plugs fitting.